Survival of halophilic Archaea in Earth's cold stratosphere. Issue 4 (27th October 2016) - DasSarma, P.; Laye, V.J.; Harvey, J.; Reid, C.; Shultz, J.; Yarborough, A.; Lamb, A.; Koske-Phillips, A.; Herbst, A.; Molina, F.; Grah, O.; Phillips, T.; et al.
Abstract: Halophilic Archaea are known to tolerate multiple extreme conditions on Earth and have been proposed as models for astrobiology. In order to assess the importance of cold-adaptation of these microorganisms in surviving stratospheric conditions, we launched live, liquid cultures of two species, the mesophilic model Halobacterium sp. NRC-1 and the cold-adapted Antarctic isolate Halorubrum lacusprofundi ATCC 49239, on helium balloons. After return to Earth, the cold-adapted species showed nearly complete survival while the mesophilic species exhibited slightly reduced viability. Parallel studies found that the cold-adapted species was also better able to survive freezing and thawing in the laboratory. Genome-wide transcriptomic analysis was used to compare the two haloarchaea at optimum growth temperatures versus low temperatures supporting growth. The cold-adapted species displayed perturbation of a majority of genes upon cold temperature exposure, divided evenly between up-regulated and down-regulated genes, while the mesophile exhibited perturbation of only a fifth of its genes, with nearly two-thirds being down-regulated. These results underscore the importance of genetic responses of H. lacusprofundi to cold temperature for enhanced survival in the stratosphere.